The Influence Of The School Environment On Students' Learning Motivation In Private Madrasah Aliyah Hidayah Of The Khalipah Bookie - Hariani, Endang Sri; Nasution, Herry Syahbannuddin (STAI Tebing Tinggi Deli, 2023)
This research approach is a quantitative approach, namely research where the data obtained is related to numbers which causes the use of statistical analysis techniques. The results of the research in this thesis, the school environment at Madrasah Aliyah Hidayah Private Bandar Khalipah is in the